Role of agrobiodiversity in family mixed systems of agriculture and pastoral livestock in the argentina pampean region: its importance for the agroecosystems sustainability - Iermanó, María José; Sarandón, Santiago Javier (Revista Brasileira de Agroecologia, 2016)
The Pampas region experiences changes in the productive model towards greater agriculturization. This is displacing mixed family systems of agriculture and pastoral livestock, maintaining high levels of agrobiodiversity that favor the fulfillment of ecological services necessary to reduce the use of inputs. The aim of this paper was to analyze the importance of these systems in the maintenance of agrobiodiversity and sustainable management. Energy efficiency for soybean and sunflower production were compared between agricultural business (AE) and mixed family (MF) systems. Shannon index, applied to cultivated species and their relative surface, and perimeter/area ratio was calculated. Energy efficiency and agrobiodiversity were higher in MF systems, while the energy inputs had a variable behavior. Proper management of agricultural biodiversity could benefit the potential of biotic regulation, but this not always resultsin less use of energy, because the difficulty in understanding the levels of agricultural biodiversity and its necessary potential to sustainable management.